Beyond formal R&D: firm’s capabilities and its innovation profile. The case of Argentinean manufacturing firms (2014-2016) - Barletta, Florencia; Suarez, Diana; Yoguel, Gabriel; Fiorentin, Florencia (Estudios de Economía, 2024)
The purpose of this article is to analyse the relationship between different innovation profiles, capabilities, and innovation results of manufacturing firms from Argentina. The premise that guides our research is that most of firms not performing formal R&D -92%- are a highly heterogeneous group in terms of innovative behaviour, capabilities and innovative performance. Thus, we propose to study firms’ innovation profile as a gradient that accounts for formal R&D, informal R&D, non- R&D performing firms and firms without innovation efforts. Then, the relationship between these profiles and five dimensions of firms’ capabilities -productive, organizational, connectivity, and accumulated and potential absorptive - is explored. Accordingly, the study of how these profiles correlate with firms’ innovation results -products and/or processes innovations, new marketing and/or organizational changes, patents and ratio of new product sales to total sales- is also carried out. The empirical evidence is based on Argentinean manufacturing firms with data from the second wave of the National Innovation Survey composed by around 4000 observations for the period of 2014-16. Results suggest that more complex R&D profiles require higher levels of capabilities. Moreover, there seems to be a threshold of capabilities in moving from the non-R&D to the informal R&D profile. Likewise, while informal R&D is a critical threshold to increase the probability of obtaining product, process, organization and marketing innovations, formal R&D is key to get patents and to increase the share of new products on total sales.